Guinness World Records 2009 - Editor-in-Chief: Glenday, Craig (United Kingdom Guinness World Records Ltd., 2008)
Guinness World Records 2009 is packed with 1000's of new records, amazing 3D photography, fold-out features including Harry Potter, the Moon Landings and 3D Dinosaurs, celebrity interviews and 100% new photography.
Include Illustration
Lists records, superlatives, and unusual facts in the areas of fame, the natural world, exploration, technology, remarkable activities, the arts, amusements, and sports, including a few special spreads "with all-new 3-D photography."
Keywords: World records -- Curiosities and wonders -- Questions and answers -- Video games